Articular cartilage: evaluation with fluid-suppressed 7.0-T sodium MR imaging in subjects with and subjects without osteoarthritis - Madelin, Guillaume; Babb, James; Xia, Ding; Chang, Gregory; Krasnokutsky, Svetlana; Abramson, Steven B; Jerschow, Alexej; Regatte, Ravinder R (Radiology, 2013)
To assess the potential use of sodium magnetic resonance (MR) imaging of cartilage, with and without fluid suppression by using an adiabatic pulse, for classifying subjects with versus subjects without osteoarthritis at 7.0 T. The study was approved by the institutional review board and was compliant with HIPAA. The knee cartilage of 19 asymptomatic (control subjects) and 28 symptomatic (osteoarthritis patients) subjects underwent 7.0-T sodium MR imaging with use of two different sequences: one without fluid suppression (radial three-dimensional sequence) and one with fluid suppression (inversion recovery [IR] wideband uniform rate and smooth truncation [WURST]). Fluid suppression was obtained by using IR with an adiabatic inversion pulse (WURST pulse). Mean sodium concentrations and their standard deviations were measured in the patellar, femorotibial medial, and lateral cartilage regions over four consecutive sections for each subject. The minimum, maximum, median, and average means and standard deviations were calculated over all measurements for each subject. The utility of these measures in the detection of osteoarthritis was evaluated by using logistic regression and the area under the receiver operating characteristic curve (AUC). Bonferroni correction was applied to the P values obtained with logistic regression. Measurements from IR WURST were found to be significant predicators of all osteoarthritis (Kellgren-Lawrence score of 1-4) and early osteoarthritis (Kellgren-Lawrence score of 1 or 2). The minimum standard deviation provided the highest AUC (0.83) with the highest accuracy (>78%), sensitivity (>82%), and specificity (>74%) for both all osteoarthritis and early osteoarthritis groups. Quantitative sodium MR imaging at 7.0 T with fluid suppression by using adiabatic IR is a potential biomarker for osteoarthritis.